REPRESENTASI PEREMPUAN DALAM FILM PENDEK “TILIK” [Representation of Women in Short Movie Titled “Tilik”] - Annisa Nur Hanifah; Rivga Agusta (Universitas Bunda Mulia, 2021)
The short film titled Tilik was produced by Ravacana Films in collaboration with the Yogyakarta Special Region Cultural Service in 2018 and this film was directed by Wahyu Agung Prasetyo. Film Tilik presents the social reality of women through the story of village women who are the main characters. The ladies' gossipy chatter was marked along the way. From a different perspective, this film tries to break the stereotype that rural women cannot have good careers but only become housewives. The purpose of this research is to find out how women are represented in the short film Tilik. This research uses Roland Barthes' semiotic analysis by looking for denotative and connotative meanings contained in the film that represent women in this film. Women are depicted as being very complex in this Tilik film, ranging from women who like to talk about other people's badness, women have positions to the negative status of unmarried or single women. The results of this study indicate that there are signs that represent women, including that women are fond of gossiping or gossiping which is depicted by the figure of Bu Tejo, the negative status of single women displayed by the figure of Dian who is always talked about by mothers, women can have positions or the position displayed by the figure of the village head, the culture of seeing the groups of mothers, and the image of women in the media.